Effective Solutions for Moving Objects in Acceleration Functions and Their Reflections Using Goen's Distance Formula - Goenawan, Stephanus Ivan (Cylinder : Jurnal Ilmiah Teknik Mesin, 2024)
Goen's distance formula effectively calculates the distance from acceleration, which has a pattern as a symmetric function of time changes. In Goen's distance formula, where the acceleration function against time has a symmetric pattern, it can be solved simply by performing a total integral and multiplying it by half of the total time. Symmetric acceleration functions can be constructed by combining certain functions with their reflections. In this study, the method of proving Goen's distance formula is carried out mathematically using single and double-level average integrals of symmetric functions. The advantage of Goen's distance formula compared to the conventional distance formula is that in finding the distance traveled by an object moving with a symmetric acceleration function, it will be more effective because it is sufficient to perform an integral once compared to having to do two integrals as done in the conventional method.